(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to determine the impact of marketing on the profitability of poultry production projects in Al-Muthanna Governorate and the study of the cost of production of meat broilers. The research sample represents (35%) of the research community, which represents the projects related to the research subject. The results of the research showed that there is an effect of the marketing process on the profit achieved through the sale of one meal production, and the results were obtained by using the statistical program (SPSS.V.22) by analyzing the simple regression function (SRA)to the research variables and analyzed the factors affecting marketing for the purpose of achieving the maximum profitability of those important projects which are an important part in the selfsufficiency of poultry meat in the province and cover part of the food security of the province ,the research has been reached a set of recommendations, including the need to address the cases of losses that occur during the raising of the meal, which caused Losses and the development of a mechanism refer to the marketing process for the product as well as the consumer, in addition to the need to provide specialized poultry marketing centers for those projects.